Plasmapheresis, Rituximab, and Ceftriaxone Provided Lasting Improvement for a 27-Year-Old Adult Male with Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS) - Krouse, Adam; Li, Huihua; Krenzer, Joseph A.; Rose, William Nicholas (Case Reports in Psychiatry, 2021)
Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS) is a specific autoimmune response to group-A streptococcal (GAS) infections in children and adolescents with a sudden onset of neuropsychiatric disorders including obsessive-compulsive disorder (OCD) or tic-like symptoms. We present a case report of a 27-year-old male patient who had lasting improvement with plasmapheresis, rituximab, and ceftriaxone. Our patient first developed sudden psychosis and confusion after GAS infections at age 17. He had elevated anti-streptolysin O (ASO) titers, negative urine drug screen, no ETOH in blood, normal CBC, normal TSH, normal salicylate, normal acetaminophen, and a normal head CT. The tentative diagnosis of PANDAS was made, and the patient was thereafter treated with antipsychotics, antibiotics, tonsillectomy, and IVIG which resulted in remissions and relapses of his neuropsychiatric symptoms. Once he reached age 27, he received a trial of therapeutic plasma exchange (TPE), rituximab, and ceftriaxone. This eventually resulted in sustained benefit and minimal fluctuations of his clinical symptoms. Our report is noteworthy in three ways.One, he is a 27-year-old adult with PANDAS.Two, he improved after TPE, rituximab, and ceftriaxone. Our literature search yielded minimal data on the use of plasmapheresis for nonteenage adults with PANDAS. Three, he had unusual symptoms of PANDAS, as the typical OCD and/or tic-like symptoms were not observed.